Answer:
56
Step-by-step explanation:
6 : 13
x : 117
117 /13 = 9
6 * 9 = 56
HOPE THIS HELPS
PLZZ MARK BRAINLIEST
1.8
2
Answer:
2
Step-by-step explanation:
Working
The nth term of an arithmetic series is calculated using the formula
nth term= a+ (n-1) d
a= -5, n =10 and nth term in this case is 13
Thus
13= -5 +(10-1)d
13= -5+9d
9d= 18
d = 2
What is (2 + 0.4 + 0.6)= ?
Answer:
Whatis(2+0.4+0.6)
First we have to arrange the numbers in sequence...
Here I have taken this 0 after the point ..as the rest of the digit are in tenths place or after the point...
The answer is 3.
We will not calculate the 0 as it does not have any value.
Ans) 3
Remark
This requires some sort of constant that each of the ratio members is multiplied by.
Call the constant x
Equation
2x + 3x + 7x = 90 Add the left hand side
Solution
12x = 90 Divide by 13
x = 90 /12
x = 7,5
Answer
2x = 2 * 7.5
2x = 15
3x = 22.5
7x = 52.5
Sum = 90 as it should be